2015
DOI: 10.3855/jidc.6504
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Vi polysaccharide, heat-killed whole cells, and outer membrane protein of Salmonella typhi

Abstract: Introduction: Salmonella typhiVi capsular polysaccharide (ViCPS) is a licensed vaccine against typhoid fever in many countries; in Egypt, the killed whole-cell vaccine is still used. In this study, mice were used as an animal model to evaluate the immune response to ViCPS and other S. typhiantigens such as heat-killed whole cells and outer membrane protein (OMP). Methodology: The three antigens were laboratory prepared, injected into mice groups, and the humoral response was evaluated using the indirect whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Specifically, SseB and different Omp family members have been described as potential vaccine candidates in mice (200)(201)(202). SseB is also immunogenic in humans; indeed, SseB-specific CD4 ϩ T cells producing IFN-␥ are detected in the circulation of asymptomatic individuals or people previously exposed to S. Typhi (203).…”
Section: Salmonella Antigens and Their Use In Vaccine Formulationsmentioning
confidence: 99%
“…Specifically, SseB and different Omp family members have been described as potential vaccine candidates in mice (200)(201)(202). SseB is also immunogenic in humans; indeed, SseB-specific CD4 ϩ T cells producing IFN-␥ are detected in the circulation of asymptomatic individuals or people previously exposed to S. Typhi (203).…”
Section: Salmonella Antigens and Their Use In Vaccine Formulationsmentioning
confidence: 99%
“…Furthermore, heat-killed aro-deficient Salmonella expressing fragment C (under control of the tac promoter)failed to induce immune responses (12). In contrast, many previous studies reported that heat-killed Salmonella is a potential vaccine against salmonellosis (2,(20)(21)(22). The source of these discrepancies is not known.…”
Section: Discussionmentioning
confidence: 87%